The anterior uterocervical angle as a new ultrasound marker of preterm labor in pregnant women with a history of endocrine and combined infertility - L.E. Tumanova; O.V. Kolomiiets (Publishing House TRILIST, 2021)
In women with endocrine and concomitant infertility there is a high frequency of the threat of termination of pregnancy at different periods, most often after stimulation of ovulation or as a result of assisted reproductive technologies, due to the formation of insufficiency of the luteal phase of the cycle in combination with hyperandrogenism and functional cervical insufficiency in every third pregnant woman. Regardless of the reasons, today there are no clear and early diagnostic criteria for this complication of pregnancy. Research objective: to determine the informational significance of the uterocervical angle for predicting premature birth in women with a singleton pregnancy and a history of infertility. Materials and methods. 127 women with singleton pregnancies aged 20-49 years underwent ultrasound at 12-14 and 16-20 weeks of gestation. The distribution of pregnant women into groups was based on the infertility factor: group I included 35 women with a history of endocrine infertility, group II included 37 pregnant women with a history of tubal-peritoneal infertility, group III included 25 women with a history of combined infertility (tubal-peritoneal infertility with endocrine), IV group (control) consist of 30 healthy pregnant women without a history of infertility. Results. The frequency of the uterocervical angle > 96° in the first half of pregnancy was in 31.4% of pregnant women with a history of endocrine infertility, in 10.8% of women with tubal-peritoneal infertility and in 32% of patients with a history of combined infertility. Preterm birth occurred in 45.4% of women with a history of endocrine infertility, in 75% of pregnant women with tubal-peritoneal infertility, in 62.5% of women with a history of combined infertility when the uterinecervical angle > 96° was detected in the first half of pregnancy. Conclusions. The uterocervical angle detected by ultrasound cervicometry in the first half of pregnancy in combination with other cervical parameters (length, state of the internal pharynx, etc.) improves the diagnosis of cervical insufficiency.